Perancangan Identitas Visual dan User Interface Aplikasi JUALOMBOK - Sukreni Mulya Agustin; Sandi Justitia Putra (Puslitbang Sekawan Institute Nusa Tenggara, 2020)
The development of technology and multimedia at this time has been developing rapidly, severalmultimedia applications have also been created and used in various fields. One of its uses is inthe field of e-commerce. Jualombok application is one of the e-commerce that is developing inLombok Island, but it is still tricky in establishing visual identity. In building the right use, acompany needs a visual identity and the correct User Interface for its application. Therefore, inthis study, the author will design a visual identity and User Interface for the JUALOMBOKApplication for the Jualombok marketplace application that has a focus on helping entrepreneurson the island of Lombok develop local MSMEs to promote and sell their products. Thisapplication was designed on November 13, 2017, by one of the companies in the city of Mataram,namely Cv. Sol Interactive. However, the design stage is only limited to the plan because theessential company is information technology, multimedia, and system integration. This researchis a qualitative study by conducting interviews with the company to get the data needed by theauthor relating to the company and the application of Jualombok. The concept used in this studyis the concept of local wisdom in the visual form and color of the logo for the user interfacecharacteristic of the island of Lombok in the log-in display on the user.User Interface Design Juallombok application presents a typical photo of the island of Lombok,namely rice barns and Songket cloth from the Sasak tribe, so that users still recognize thisapplication as an original application made by the company on Lombok Island despite having amodern look. So that both the visual identity and user interface will still remind the audience onthe island of Lombok, following what is desired by the company